Genetic risk for asthma, allergic rhinitis, and atopic dermatitis. - Dold, S (1992)
In order to explore the genetic risk of a child with a family history of allergies developing asthma, allergic rhinitis, or atopic dermatitis, questionnaires filled in by 6665 families were analysed. The data were collected in a population based cross sectional survey of 9-11 year old schoolchildren living in Munich and southern Bavaria. The relation between asthma, allergic rhinitis, and atopic dermatitis and the number of allergic first degree relatives, and the type of allergic disease was examined. Analyses were done separately for families with single or multiple allergic diseases. In families with one allergic parent the risk of the child developing asthma was increased by asthma in a parent, with an odds ratio (OR) of 2.6 (95% confidence interval 1.7 to 4.0) but not by parental allergic rhinitis with OR 1.0 (0.7 to 1.5) or atopic dermatitis, OR 1.0 (0.6 to 1.6). For allergic rhinitis the highest risk with OR 3.6 (2.9 to 4.6) was observed with allergic rhinitis of one parent, apparently lower for asthma of one parent, OR 2.5 (1.6 to 4.0) or atopic dermatitis, OR 1.7 (1.1 to 2.5). Children with parental atopic dermatitis had a high risk for atopic dermatitis, OR 3.4 (2.6 to 4.4), compared with children with parental asthma, OR 1.5 (1.0 to 2.2), or parental allergic rhinitis, OR 1.4 (1.1 to 1.8). Risk factors in families with combined allergies of two relatives (parents and siblings) were analysed separately for the different combinations. These results support the hypothesis that asthma, allergic rhinitis, and atopic dermatitis are multifactorial diseases brought about by various familial and environmental influences.